PERAN HUKUM ADMINISTRASI NEGARA DALAM MENGATASI KONFLIK AGRARIA DI INDONESIA - Raihan Brilliawan (Journal of Law and Justice, 2025)
Agrarian conflicts in Indonesia are complex issues involving various legal, social, and economic aspects. This study, entitled "The Role of State Administrative Law in Resolving Agrarian Conflicts in Indonesia," is motivated by the prevalence of land disputes, often caused by unequal land ownership, overlapping policies, and weak implementation of administrative law. The issues raised in this study include how State Administrative Law regulates government authority in resolving agrarian disputes and the effectiveness of the application of general principles of good governance (AUPB) in addressing these issues. This study aims to analyze the role of administrative law in strengthening the agrarian dispute resolution system through a normative juridical approach using case studies and legal document analysis. The results show that although agrarian regulations are in place, their implementation still faces challenges in the form of abuse of authority, ineffective bureaucracy, and minimal oversight. The conclusions of this study emphasize the need for land policy reform, capacity building of legal institutions, and strengthening transparency and public participation in administrative processes. With the effective implementation of administrative law, it is hoped that agrarian conflicts can be minimized, thereby achieving social justice and legal certainty in Indonesia.